Component breakage after total knee arthroplasty: a narrative review. Issue 6 (November 2020) - Biggi, Stefano; Capuzzo, Andrea; Tedino, Riccardo; Cattaneo, Gabriele; Tornago, Stefano; Camera, Andrea
Abstract : Component breakage is a rare complication after total knee arthroplasty (TKA). Fracture can occur in the metallic components or the polyethylene liner. Polyethylene liner fractures are the most frequent and usually belong to the tibial post because of trauma or excessive rotational forces in malaligned implants. In metallic components, the most frequent pattern is stress-fatigue fracture in the thinner areas, when exposed to greater loads. Specifically, these occur in the junction between the distal and medial surfaces of the medial condyle of the femur or the area between the stem and the medial plateau in the tibial tray. Common clinical findings are swelling, loss of motion, varus collapse, and patellar clunk syndrome. Diagnosis is relatively easy and includes clinical examinations and standard radiographs. The treatment is surgical and can hide pitfalls, especially if the surgical timing is incorrect. In addition to the revision of one or more components, surgeons must address any issues for the management of bone defects and ligamentous stability.